2021
DOI: 10.3390/ma14206129
|View full text |Cite
|
Sign up to set email alerts
|

Application of Variational Method to Stability Analysis of Cantilever Vertical Plates with Bimodular Effect

Abstract: In the design of cantilevered balconies of buildings, many stability problems exist concerning vertical plates, in which reaching a critical load plays an important role during the stability analysis of the plate. At the same time, the concrete forming vertical plate, as a typical brittle material, has larger compressive strength but lower tensile strength, which means the tensile and compression properties of concrete are different. However, due to the complexities of such analyses, this difference has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is easy to see that they are quite close. In fact, in the previous study [ 32 ], the variational method was successfully used in the analysis of stability of cantilever vertical plates with different moduli. In addition, the recent study [ 33 ] also showed that, for the large deformation of thin shallow spherical shells, the perturbation solution agrees well with the variational solution.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to see that they are quite close. In fact, in the previous study [ 32 ], the variational method was successfully used in the analysis of stability of cantilever vertical plates with different moduli. In addition, the recent study [ 33 ] also showed that, for the large deformation of thin shallow spherical shells, the perturbation solution agrees well with the variational solution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that the displacement variational equation itself represents the equilibrium equation and stress boundary conditions, it naturally avoids the consideration for the equilibrium condition of thin plates, while in the perturbation method, the establishment of an equation of equilibrium is necessary and somewhat complicated. Recent studies [31,32] also indicated that the variational method can be successfully used in the analysis of plates and shells. First, Xue et al [31] adopted the variational method to obtain the critical loads of cantilever vertical plates with different moduli.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [31,32] also indicated that the variational method can be successfully used in the analysis of plates and shells. First, Xue et al [31] adopted the variational method to obtain the critical loads of cantilever vertical plates with different moduli. Thereafter, He et al [32] also used the variational method to solve bimodular thin shells under large deformation.…”
Section: Introductionmentioning
confidence: 99%